Factors Correlated with the Intention of Iron Tablet Consumption among Female Adolescents - Riri Aprianti; Gadis Meinar Sari; Tiyas Kusumaningrum (Jurnal Ners, 2018)
Introduction: Anaemia in female adolescents tends to have a negative impact that is likely to later arise in pregnancy, labour and childbirth. The prevalence of iron deficiency anaemia in female adolescents in Indonesia is thirty percent. Indonesia runs an iron tablet program for female adolescents. However, with the running of the program, it is not clear what factors are correlated with the intention of iron tablet consumption among female adolescents. The purpose of this study was to analyse the factors correlated with the intention of iron tablet consumption among female adolescents.Methods: This research used a cross-sectional design. The sample consisted of 100 students in senior high school in Surabaya, chosen by proportional random sampling. The independent variables were parent income, knowledge, perceived susceptibility, perceived seriousness, perceived threats, perceived benefits, perceived barriers, and perceived self-efficacy. The dependent variable was female adolescent intention related to consuming iron tablets. The data was collected using a questionnaire and analysed by a chi square test with a level of significance α<0.05.Results: There was a significant correlation between perceived threat (p=0.02), perceived benefit (p=0.01), perceived barrier (p=0.02) and perceived self-efficacy (p=0.00) and female adolescent intention related to consuming iron tablets. There was no correlation between parental income, adolescent knowledge, perceived susceptibility, and perceived seriousness with the intention to consume iron tablets.Conclusion: From this research, it has been concluded that the factors related to the intention to consume iron tablets in female adolescents were perceived threat, perceived benefit, perceived barrier and perceived self-efficacy. Increasing the confidence of female adolescents in association with the importance of avoiding anaemia by consuming iron tablets is crucial so then they can maintain their health and prevent diseases due to anaemia later on.